Long-term impact of a 4-day feed restriction at the protozoea stage on metabolic gene expressions of whiteleg shrimp (Litopenaeus vannamei) - Lage, Luis Paulo A.; Weissman, Delphine; Serusier, Mélanie; Putrino, Soraia Marques; Baron, Frederic; Guyonvarch, Alain; Tournat, Mathieu; Nunes, Alberto Jorge Pinto; Panserat, Stephane (PeerJ, 2020)
Based on the “nutritional programming” concept, we evaluated the long-term effects of an early four-day caloric restriction (40% reduction in feed allowance compared to a normal feeding level) at the protozoea stage in whiteleg shrimp. We analyzed long-term programming of shrimp by studying metabolism at the molecular level, through RT-qPCR of key biomarkers (involved in intermediary metabolism and digestion). The mRNA levels (extracted from the whole body) were analyzed after the stimulus and after the rearing period, at 20 and 35 days, respectively. At the end of the experimental period, shrimp growth performance was evaluated. There was no difference between normal feed allowance (CTL) and feed-restricted shrimp (RES) for performance parameters (survival, final body weight and the number of post-larvae g−1 or PL g−1). The stimulus directly affected the mRNA levels for only two genes, i.e., preamylase and lvglut 2 which were expressed at higher levels in feed-restricted shrimp. In the long-term, higher levels of mRNAs for enzymes coding for glycolysis and ATP synthesis were also detected. This suggests a possible long-term modification of the metabolism that is linked to the stimulus at the protozoea stage. Overall, further studies are needed to improve nutritional programming in shrimp.
Keywords: Feed restriction; Gene expression; Digestion; Whiteleg shrimp; Metabolism; Programming